Do Culinary Preferences Vary Across Generations? Yogyakarta Experiences - Suci Sandi Wachyuni; Nenny Wahyuni; Shinta Teviningrum; Kadek Wiweka; Murhadi (Journal of Tourism and Economic, 2024)
The purpose of this research is to determine the culinary preferences of tourists in each generation, namely generation X, generation Y, and generation Z in Yogyakarta. Each generation has significant characteristic differences, as well as their culinary preferences. Generation X likes the practical nature of making consecutive visits to one restaurant that they think suits their taste. Generation Y tends to choose classy food with a fairly expensive price range which is in accordance with those who are at the peak of their careers. Generation Z will choose food by placing an order on an online application because of the high amount of using gadgets. To find out more about culinary preferences, a demographic segment analysis was carried out in each generation using quantitative research on data collection through library research and questionnaire surveys. Therefore, this research is expected to provide understanding and knowledge to readers regarding the culinary preferences that tourists are interested in each generation group, namely Y Generation, and Z Generation.